2015
DOI: 10.3390/ijerph120100970
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Virulence Determinants and Antimicrobial Resistance among Commensal Escherichia coli Derived from Dairy and Beef Cattle

Abstract: Cattle is a reservoir of potentially pathogenic E. coli, bacteria that can represent a significant threat to public health, hence it is crucial to monitor the prevalence of the genetic determinants of virulence and antimicrobial resistance among the E. coli population. The aim of this study was the analysis of the phylogenetic structure, distribution of virulence factors (VFs) and prevalence of antimicrobial resistance among E. coli isolated from two groups of healthy cattle: 50 cows housed in the conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 43 publications
10
22
0
Order By: Relevance
“…1). These findings are basically concordant with the previous finding that most bovine commensal isolates belonged to phylogroups B1 and A (Bok et al 2015;Madoshi et al 2016;Mercat et al 2016). As for human commensal isolates, it was reported that B2 strains predominate in people residing in developed countries in the temperate regions of the world (Escobar-Paramo et al 2004;Skurnik et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…1). These findings are basically concordant with the previous finding that most bovine commensal isolates belonged to phylogroups B1 and A (Bok et al 2015;Madoshi et al 2016;Mercat et al 2016). As for human commensal isolates, it was reported that B2 strains predominate in people residing in developed countries in the temperate regions of the world (Escobar-Paramo et al 2004;Skurnik et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Phylogenetic Groups B1 and D, and virulence Group Ia were specific among patients and cattle strains in Cluster 2, which confirmed the results of our previous study (Wang et al 2013). Bok et al (2015) also observed that the phylogenetic Group B1 was predominant among isolates from beef cattle; similarly, an Australian survey (Staples et al 2013) reported that the majority of EPEC strains fell into Group B1. Together, these findings suggested that cattle are a major source of strains that are diarrhoeagenic in humans, particularly for strains of Group B1.…”
Section: Discussionsupporting
confidence: 89%
“…Bok et al . () also observed that the phylogenetic Group B1 was predominant among isolates from beef cattle; similarly, an Australian survey (Staples et al . ) reported that the majority of EPEC strains fell into Group B1.…”
Section: Discussionsupporting
confidence: 52%
“…The results observed in this study are in agreement with studies done in Ethiopia, Iran, and Pakistan [4144]. Meanwhile, our findings contradict findings of earlier studies done in South Africa and Poland that reported lower prevalences [25,29].…”
Section: Discussionsupporting
confidence: 88%
“…The other reason could be the co-selection of resistant determinant and co-resistance of the E. coli isolates. The simultaneous resistance to penicillin, streptomycin, tetracycline, erythromycin, kanamycin, and virginiamycin has been reported in studies conducted elsewhere [2931]. A similar co-selection of sulphonamide resistance genes was reported in chickens treated with streptomycin [32].…”
Section: Discussionsupporting
confidence: 54%